Discovering the Intended Meaning of Figurative Languages in Damian Marley’s Song Lyrics - Silvester Aman; Desak Putu Eka Pratiwi; Ni Wayan Suastini (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
The objectives of this study are to find out types of figurative language and their intended meanings. There are two theories that used in this research. The first theory is proposed by Knickerbocker and Reninger (1974) which is used to find out types of figurative language used in Damian Marley’s song lyrics. The second theory is proposed by Leech (1981) which is used to find out the meaning of figurative language used in Damian Marley’s song lyrics. The method used in collecting the data was observation method. The writer collected the data of song lyrics by browsing and downloading song lyrics from the internet, reading and understanding song lyrics, taking note and classifying the data based on type’s figurative language. The writer analysed the data descriptively by using qualitative method. After analyzing the data, the writer found that there are six types of figurative language used in Damian Marley’s song lyrics which consist of 3 metaphors (19%), 5 similes (32%), 2 irony (12%), 3 allusion (19%), 1 synecdoche (6%), and 2 metonymies (12%). All of the figurative language have connotative meaning which implicitly deliver hidden messages and life values.